When the head aches, the body aches: use and abuse in the appointment of positions in the government of the New Kingdom of Granada (late 17th century) - Velasco Pedraza, Julian Andrei (Universidad Pedagógica y Tecnológica de Colombia, 2019)
This article analyses the appointment of positions of the superior government of the New Kingdom of Granada and the accusations regarding the abuses perpetrated there by the president governors. It is possible to explain this phenomenon in virtue of the cultural circumstances of the time, in which distributive justice (as an obligation of the king and his representatives towards their vassals) such as the reciprocity of social ties (don and contradon) were combined. The methodology used consisted of consulting various normative and institutional sources from a historical-legal and political- cultural perspective, in order to understand the uses and abuses of the appointment of positions in this context. It was possible to ascertain that knowledge of the quotidian institutional mechanisms allows for a better understanding of the way in which those who provided the positions tried to support the obligations of their position and those of their social ties.